2020
DOI: 10.1002/btpr.3108
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of continuous processing for manufacturing of biotherapeutics

Abstract: Continuous processing offers a promising approach to revolutionize biotherapeutics manufacturing as reflected in recent years. The current study offers a comparative economic assessment of batch and continuous processing for the production of biotherapeutic products. Granulocyte-colony stimulating factor (GCSF), a protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
(73 reference statements)
1
32
0
Order By: Relevance
“…While this range has yet to account for the capital cost and processes other than the cultivation unit, this value is still less than 1% of the market price of Opdivo. Our result agrees with other studies that manufacturing cost presents a trivial fraction of the final selling value . However, lowering the manufacturing cost can contribute to higher flexibility in price setting, increased drug access in lower income regions, and fending off competition after patent expiry.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While this range has yet to account for the capital cost and processes other than the cultivation unit, this value is still less than 1% of the market price of Opdivo. Our result agrees with other studies that manufacturing cost presents a trivial fraction of the final selling value . However, lowering the manufacturing cost can contribute to higher flexibility in price setting, increased drug access in lower income regions, and fending off competition after patent expiry.…”
Section: Resultssupporting
confidence: 92%
“…Our result agrees with other studies that manufacturing cost presents a trivial fraction of the final selling value. 60 However, lowering the manufacturing cost can contribute to higher flexibility in price setting, increased drug access in lower income regions, and fending off competition after patent expiry. Therefore, cost reductions must be achieved wherever possible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Economic analyses of continuous biomanufacturing coupled with continuous chromatographic processes (referred to as integrated continuous processing) can reduce costs by 55% compared to conventional batch processing, when both capital and operating expenses are considered. 59,60 Indeed, a recent analysis suggests that commercial scale continuous process production could achieve COGs of $25/g. 60 Historically, 12-18 months has been the rule of thumb for estimating the time from the availability of mAb genes to release of GMP material; however, new strategies using transient expression for supply of Phase 1 drug while establishing a GMP stable clone for later stages of development may become more common and is the strategy that enabled multiple mAb drugs to rapidly enter clinical trials for COVID-19.…”
Section: Mammalian Cell Culturementioning
confidence: 99%
“…59,60 Indeed, a recent analysis suggests that commercial scale continuous process production could achieve COGs of $25/g. 60 Historically, 12-18 months has been the rule of thumb for estimating the time from the availability of mAb genes to release of GMP material; however, new strategies using transient expression for supply of Phase 1 drug while establishing a GMP stable clone for later stages of development may become more common and is the strategy that enabled multiple mAb drugs to rapidly enter clinical trials for COVID-19.…”
Section: Mammalian Cell Culturementioning
confidence: 99%
“…Over the last 10 years, considerable work has been done in this field by both academia and industry. It has been demonstrated that switching from batch to continuous processing can increase productivity by about 10× and reduce the cost of goods by 50-70% [27]. These benefits are realizable based on the need for a significantly smaller facility (and thereby reduced capital cost), improved facility utilization, streamlined process flow, improved process control, and more consistent product quality.…”
Section: Improving Manufacturing Technology For Biopharmaceutical Productionmentioning
confidence: 99%